2022
DOI: 10.18332/popmed/150644
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of US adult opinions on restricting exposure of children to smoking in movies: The 2020 Health Information National Trends Survey

Abstract: INTRODUCTIONLegislative policies aimed at curbing early exposure to smoking among youth are a crucial public health strategy. Yet little is known about US adults' public opinion on restricting exposure of children to movies depicting smoking. This study sought to characterize US adults' levels of support to restrict the exposure of children to smoking in movies and explore associations with sociodemographic characteristics. METHODS We used cross-sectional data from the 2020 Health Information National Trends S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…This study sought to expand the literature on this issue by assessing the extent to which U.S. adults are supportive, neutral, or opposed to a default R-rating policy for movies with cigarette smoking; it also explored various predictors of support, neutrality, and opposition toward such a policy. Our findings indicate that almost half (48.2%) of U.S. adults support a R-rating policy for movies depicting cigarette use, which is relatively close to the upper limit (40.0%–48.2%) of what has been reported in other studies (Blake et al, 2010; Lama et al, 2022; McMillen, 2020; Oghenetega et al, 2022). We also found that there is more neutrality than opposition (31.1% vs. 20.7%) to such a policy, which could be due to a lack of public understanding regarding the link between depictions of cigarette smoking in movies and subsequent youth smoking initiation.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This study sought to expand the literature on this issue by assessing the extent to which U.S. adults are supportive, neutral, or opposed to a default R-rating policy for movies with cigarette smoking; it also explored various predictors of support, neutrality, and opposition toward such a policy. Our findings indicate that almost half (48.2%) of U.S. adults support a R-rating policy for movies depicting cigarette use, which is relatively close to the upper limit (40.0%–48.2%) of what has been reported in other studies (Blake et al, 2010; Lama et al, 2022; McMillen, 2020; Oghenetega et al, 2022). We also found that there is more neutrality than opposition (31.1% vs. 20.7%) to such a policy, which could be due to a lack of public understanding regarding the link between depictions of cigarette smoking in movies and subsequent youth smoking initiation.…”
Section: Discussionsupporting
confidence: 83%
“…Finally, each respondent’s political viewpoint was assessed using the item: “Thinking about politics these days, how would you describe your own political viewpoint?” The original response categories included: “very liberal,” “liberal,” “somewhat liberal,” “moderate,” “somewhat conservative,” “conservative,” and “very conservative.” Due to the small cell counts for certain subcategories and for analysis purposes, we recoded the responses into three categories: “liberal” (very liberal, liberal, somewhat liberal), “moderate,” and “conservative” (very conservative/ conservative/ somewhat conservative). Furthermore, given that “social media” can be used as a platform for tobacco-specific communication designed to increase policy support (Oghenetega et al, 2022), we included this variable in our analysis. We assessed each respondent’s social media use using the item: “In the last 12 months, have you used the internet to visit a social networking site, such as Facebook or LinkedIn?” The response categories were “yes” and “no.”…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation